A Case Study of Applying a Capacity Building Program to Sport Life Skill Leaders - Yunkyung Yang; Taehee Lim; Ohjung Kwon; Junsu Bae (Korea Institute of Sport Science, 2022)
PURPOSE This study aimed to apply a capacity building program to sport life skill leaders and to provide cases of this process. METHODS The study participants included four leaders (male=2, female= 2, Mage=37.5) who were managing a sport life skills program at a university. They participated in a capacity building program, which consisted of (a) understanding (leader seminar), (b) application (managing the sport life skills program), and (c) evaluation (leader's self-reflection), which were conducted in eight sessions. Four leaders conducted self-evaluations using program quality assessment (PQA) during every session, and quantitative and qualitative data were collected. Qualitative data were derived using a cross-case analysis, and quantitative data were used for calculating the effect size after performing the paired t-test. RESULTS Analyzing the reported cases of sport life skill leaders, the use value of the capacity building program was identified. Furthermore, the cases reported by the four leaders enabled observation of how the leader's capabilities were strengthened. In the paired t-test, the effect size of physical and psychological safety, appropriate structure, supportive relationship, opportunities to belong, support for efficacy mattering, opportunities for life skill building, excluding integration of family, school, and community effort, were all significant. All effect sizes were found to have "very large effects." CONCLUSIONS The capacity building program played a positive role in strengthening the leaders' life skill coaching capabilities. These findings have practical implications-chiefly, it is important to strengthen leaders' or coaches' capabilities in order to foster life skill development and transfer of student-athletes.